The influence of core self-evaluation (CSE) on employees’ motivation in continuing education. - Boon, Chi Teng (2011)
Boon Chi Teng, Diana Low Foong Ling, Lim Shenn Yi, Ng Xiao Qian, Wong Pei Pei, Ms Claudia Lau Say Min